DEFINING PEDIATRIC DIABETES USING EMR RECORDS AND VALIDATION FROM LINKABLE MANITOBA COHORT DATA. (18th May 2018) - Singer, Alexander; Kosowan, Leanne; Queenan, John; Yeung, Roseanne; Amed, Shazhan; Wicklow, Brandy
Abstract: BACKGROUND: The prevalence of paediatric diabetes is increasing. Identifying and describing populations with paediatric diabetes using Primary Care Electronic Medication Records (EMR) can improve surveillance and management. OBJECTIVES: To describe the population of children diagnosed with paediatric diabetes in Manitoba using Electronic Medical Record data from Community Paediatricians and Family Physcians in Manitoba. DESIGN/METHODS: We applied a previously validated case definition for type 1 and type 2 diabetes to patients aged 1–18 seen by one of the 221 primary care providers participating in the Manitoba Primary Care Research Network (MaPCReN) between 1998–2015. We compared the agreement between the MaPCReN definition and Manitoba's Diabetes Education Resource for Children and Adolescents (DERCA) clinical database of confirmed cases. Cases were described, including prevalence, patient characteristics, and health system use. RESULTS: Our definition identified 166 children (0.4%, 95% CI 0.36% - 0.49%) of whom 53.0% lived in a rural location and 53.6% were female. The mean age at diagnosis was 11.4 years (SD 5.4). There were 90 patients identified by the definition also cared for by a paediatric endocrinologist at DERCA [sensitivity (54.2%), specificity (98.7%), and kappa (0.61, CI 0.54-.069)]. An additional 286 patients had at least one documented HbA1C of 6.5% or higher but did not have a corresponding diabetes diagnosis within the EMR. Of those, 45% had an HbA1c between 6.5 -7.5 and 25.9% had an HbA1c over 8.5%. Most of these patients also had an abnormal fasting glucose in the EMR (76.9%). There were 280 patients with an elevated HbA1c that had no evidence of attending an appointment with a paediatric endocrinologist at DERCA, 70.8% have a rural address. CONCLUSION: The inclusion of HbA1c values in identifying paediatric diabetes suggested a large number of patients without a corresponding diabetes diagnosis or record of care from DERCA. Therefore, the DERCA database might be underestimating the true prevalence of diabetes in Manitoba. Understanding further characteristics of this population, is an essential step to inform the development of enhanced services and strategies.